High geogenic soil thallium shows limited impact on bacterial community - Šťovíček, Adam; Vaněk, Aleš; Blumentrittová, Hana; Mihaljevič, Martin; Vaňková, Maria; Kopecký, Jan; Vejvodová, Kateřina; Máslová, Alena; Sagová-Marečková, Markéta (Environmental pollution (1987), 2024)
Thallium (Tl) is a highly toxic trace metal, included in the US EPA list of priority pollutants. Even though its toxicity is potentially higher or comparable to Cd or Hg, its environmental impact is largely unknown. Despite its toxicity, only a few recent studies are mapping the impact of recently introduced Tl on soil microbial communities, namely in agricultural systems but no studies focus on its long term effect. To complement the understanding of the impact of Tl on soil, this study aims to describe the influence of extremely high naturally occurring Tl concentration (50 mg/kg of potentially bioavailable Tl) on soil microbial communities. Our investigation concentrated on samples collected at Buus (Erzmatt, Swiss Jura, Switzerland), encompassing forest and meadow soil profiles of the local soil formed on hydrothermally mineralized dolomite rock, which is naturally rich in Tl. The soil profiles showed a significant proportion of potentially bioavailable Tl. Yet, even this high concentration of Tl has a limited impact on the richness of the soil bacterial community. Only the meadow soil samples show a reduced richness compared to control samples. Furthermore, our analysis of geogenic Tl contamination in the region unveiled a surprising finding: compared to other soils of Switzerland and in stark contrast to soils affected by recent mining activities, the structure of the bacterial community in Buus remained relatively unaffected. This observation highlights the unique ability of soil microbial communities to withstand extreme Tl contamination. Our study advances the understanding of Tl's environmental impact and underscores the resilience of soil microbes in the face of severe long-term contamination.
Keywords: Trace Elements; rtuť; látky znečišťující půdu; Mercury; China; Soil; půda; stopové prvky; Bacteria; thallium; Soil Pollutants; Environmental Monitoring; monitorování životního prostředí; Čína; Thallium